2020
DOI: 10.1044/2020_jslhr-20-00129
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Speech Intervention in Patients With a Cleft Palate: Comparison of Motor-Phonetic Versus Linguistic-Phonological Speech Approaches

Abstract: Purpose The purpose of this study was to compare the effect of two different speech therapy approaches, a traditional motor-phonetic approach and a linguistic-phonological approach, on the speech and health-related quality of life in Dutch-speaking children with a cleft palate with or without a cleft lip (CP ± L) between 4 and 12 years old. Method A block-randomized, sham-controlled design was used. Fourteen children with a CP ± L ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…who was related to the cleft team of the Ghent University Hospital and had 4 years of scientific and clinical experience in diagnosing and treating cleft‐related speech disorders. Both groups received speech intervention using a linguistic‐phonological approach following the principles of the Metaphon treatment with modifications for children with a CP±L (Alighieri, Bettens, Bruneel, D'haeseleer, et al., 2020; Dean et al., 1995). An individualized treatment plan was made for each patient.…”
Section: Methodsmentioning
confidence: 99%
“…who was related to the cleft team of the Ghent University Hospital and had 4 years of scientific and clinical experience in diagnosing and treating cleft‐related speech disorders. Both groups received speech intervention using a linguistic‐phonological approach following the principles of the Metaphon treatment with modifications for children with a CP±L (Alighieri, Bettens, Bruneel, D'haeseleer, et al., 2020; Dean et al., 1995). An individualized treatment plan was made for each patient.…”
Section: Methodsmentioning
confidence: 99%
“…By including additional strategies to stimulate their participation (e.g., parent reflection, role play, provision of real-time feedback from the SLP to the parents), parents can be more adequately deployed in the intervention process (Sugden et al, 2016). A recently performed randomized controlled trial, which investigated the effectiveness of two different speech therapy approaches in 14 children with a CP±L, suggested that the specific content of a therapy can influence parents' willingness to practice at home (Alighieri et al, 2020a). Findings of that study suggested that parents were more likely to practice at home when straightforward, easy and child-friendly games were provided rather than asking them to apply more complex techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, there have been few studies that have addressed how dosage and frequency impacts speech intervention outcomes (Baker & McLeod, 2011;Cummings et al, 2020) and even fewer focusing on the dosage of intervention for children with CP±L (Alighieri et al, 2020). Alighieri et al (2020) compared the effects of a traditional motor-phonetic approach and a linguistic-phonological approach on the speech outcomes of children with CP±L aged 4-12 years old. Intervention was provided by a speech and language therapist with follow-up practice at home.…”
Section: Length Frequency and Duration Of Interventionmentioning
confidence: 99%